2014
DOI: 10.1080/23256214.2014.915766
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure affects resource partitioning between pygmy and white-breasted nuthatches

Abstract: Ecologically similar, sympatric species will theoretically drive one or the other extinct unless those species can divide their resources. Resource partitioning is a common way to avoid competitive exclusion and these differences in resource utilization often represent the "ghost of competition past." I studied how two closely related species, pygmy (Sitta pygmaea) and white-breasted (Sitta carolinensis) nuthatches, divide tree space. Furthermore, I tested whether pygmy and white-breasted nuthatches foraged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…This pattern has even been detected within nuthatch species. For example, in North American ponderosa pine forests, sympatric pygmy and white-breasted nuthatches partition their resources by foraging in different parts of the tree (Stallcup 1968, McEllin 1979, Cloyed 2014. Our results confirm these findings.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This pattern has even been detected within nuthatch species. For example, in North American ponderosa pine forests, sympatric pygmy and white-breasted nuthatches partition their resources by foraging in different parts of the tree (Stallcup 1968, McEllin 1979, Cloyed 2014. Our results confirm these findings.…”
Section: Discussionsupporting
confidence: 82%
“…From this data, the author concluded that pygmy nuthatches have a foraging niche in thinned and unthinned forests that is distinct from white-breasted nuthatches, allowing them to coexist without potential population implications. Our data, consistent with the differential tree use in nuthatches reported by Cloyed (2014) and the estimated niche overlaps (including brown creepers), suggest that changes in forest structure could lead to changes in competitive dynamics among them, as discussed below.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations